ChemInform Abstract: High‐Pressure Synthesis and Characterization of the Rare‐Earth Fluoride Borate LaB2O4F. Issue 48 (26th November 2013) - Hinteregger, Ernst; Kocsis, Krisztina; Hofer, Thomas S.; Heymann, Gunter; Perfler, Lukas; Huppertz, Hubert
Abstract LaB2O4F is prepared from stoichiometric mixtures of La2O3, B2O3, and LaF3 under high‐pressure/high‐temperature conditions (BN crucibles in multianvil press, 1300 °C, 1.1 GPa).